Netcare Breast Care Centre of Excellence : what opportunity in African medical tourism? - Beswick, Claire (SAGE knowledge. Cases., 2016)
In August 2006, Dr Richard Friedland, the chief executive officer of Netcare Holdings, which operated the largest private hospital network in South Africa, was looking at the findings of research into the opportunity that medical tourists from Africa presented for the group's Breast Care Centre of Excellence. Traditional thought was that because poverty was so widespread in Africa, the possibility of attracting medical tourists from Africa to South Africa was minimal. Reading the report, Friedland now wondered whether this was indeed the case - and, if not, how the centre could exploit the opportunity such tourism presented.